Social Crises: Signatures of Complexity in a Fast-Growing Economy. (24th April 2018) - Cárdenas, Juan Pablo; Vidal, Gerardo; Urbina, Carolina; Olivares, Gastón; Rodrigo, Pablo; Fuentes, Miguel
Abstract : Social systems are always exposed to critical processes in which their organization, or part of it, is questioned by the society that demands solutions through different critical saliences. The traditional approach to such social crises has mainly focused on their anticipation and management, implying that the focus is on trying to deal with crises once they occur, rather than delving in their essential characteristics that seemingly depend on the adaptive nature of the system and the increase in its internal complexity. To address this issue, we propose a dual approach that utilizes both qualitative (documentary analysis) and quantitative methods (online social network analysis) in order to delve into the relationship between the complexity of the social system, its adaptation, and critical episodes. Our analysis shows how an explosive economic growth affects a social system, increasing its complexity. This complexity produces different demands from the system itself. These demands manifest signatures of complexity such as a heterogeneous and rich social structure, which emerges during moments when the society acts strongly.